Analysis of Academic Procrastination at Islamic University by Using Spiritual Risk Management - Ramza Husmen; Syahrur Ramli; Silvia Susrizal; Muhammad Khadafi; M Ravi Akbar; Dzaky Hafizh Muttaqien; Andieni Putri Olivia Arifin; Yusuf Baihaqi; Masruchin (ISTAWA, 2025)
This study aim to analyze academic procrastination in Islamic University. Internal factors sourced from motivation, skills and commitment. External factors sorced from environment, academic facilities, digital ethics and irrelevance academic method. These are making more impact for result of academics, finishing study and institution. Research implemented at PAI major of UIN Mahmud Yunus Batusangkar. Preliminary data on 2021/2022 academic year there are 42,2% higher student impacted on procrastination. Data collected from guided interview with head master of major and academic. The result is 51% form communication and outcome of study. Using spiritual risk management can encourage participants to improve their academic and decresing their problem. Implementation of commitment from inside and time management shoul be self efficacy. Spiritual activity can balancing for emotion, online games and bad friendship can be impactfull to reducing.